Mechanisms of the beneficial effect of sevoflurane in liver ischemia/reperfusion injury - Cavalcante,Fernanda Paula (2015)
PURPOSE: To evaluate the underlying mechanisms by which sevoflurane protects the liver against ischemia/reperfusion injury evaluate the mechanism by which sevoflurane exerts this protective effect. METHODS: Twenty-six rats were subjected to partial ischemia/reperfusion injury for 1h: one group received no treatment, one group received sevoflurane, and sham group of animals received laparotomy only. Four hours after reperfusion, levels of alanine and aspartate aminotransferases, tumor necrosis factor-a, and interleukins 6 and 10 were measured. Analyses of mitochondrial oxidation and phosphorylation, malondialdehyde content, histology, and pulmonary vascular permeability were performed. RESULTS: Serum levels of alanine and aspartate aminotransferases were significantly lower in the sevoflurane group compared to untreated controls (p<0.05). The sevoflurane group also showed preservation of liver mitochondrial function compared to untreated controls (p<0.05). Sevoflurane administration did not alter increases in serum levels of tumor necrosis factor-a, and interleukins 6 and 10. Sevoflurane treatment significantly reduced the coagulative necrosis induced by ischemia/reperfusion (p<0.05). Pulmonary vascular permeability was preserved in the sevoflurane group compared to untreated controls. CONCLUSION: Sevoflurane administration protects the liver against ischemia/reperfusion injury, via preservation of mitochondrial function, and also preserves lung vascular permeability.